Legally-informed information disclosure in early-stage ventures. (3rd October 2022) - Newell, William; Walsh, Jacqueline S.
Entrepreneurs face unique challenges during the formation of new ventures, including how to balance the tension between sharing and protecting confidential information with potential investors and customers while also ensuring the effective development of these relationships. To address this challenge, we suggest that new ventures employ the concept of legally-informed information disclosure (LID). We define LID as the sharing of sensitive and valuable information through means that, with the legal and relational environments in mind, clearly indicate its value and confidential nature before and during the process of disclosure. This conceptual paper argues that LID lies at the intersection of relational governance, contractual governance, and the legal perspective of breach of confidence. We propose a theoretical framework to illustrate this three-way relationship. Introducing the legal perspective to an established body of literature allows for an actionable framework that is inter-disciplinary, and legally and theoretically supported.